The underexplored links between cancer and the internal body climate: Implications for cancer prevention and treatment - Paul, Doru; Nedelcu, Aurora M. (Frontiers in Oncology, 2022)
In order to effectively manage and cure cancer we should move beyond the general view of cancer as a random process of genetic alterations leading to uncontrolled cell proliferation or simply a predictable evolutionary process involving selection for traits that increase cell fitness. In our view, cancer is a systemic disease that involves multiple interactions not only among cells within tumors or between tumors and surrounding tissues but also with the entire organism and its internal “milieu”. We define the organismic climate as an emergent property resulting from spatial and temporal interactions among internal components themselves and with the external environment. The organismic climate can either prevent, promote or support cancer initiation and progression (top-down effect; i.e., climate-induced effects on cancer), as well as be perturbed by cancer (bottom-up effect; i.e., cancer-induced climate changes) to further favor cancer progression and spread. This positive feedback loop can move the system towards a “cancerized” organism and ultimately results in its demise (extinction). In our view, cancer not only affects the entire system; it is a reflection of an imbalance of the entire system. This model provides an integrated framework to study all aspects of cancer as a systemic disease, but also highlights unexplored links that can be altered to both prevent climate changes that favor cancer initiation, progression and dissemination as well as reconstitute or manipulate the internal climate to hinder the success of cancer inception, progression and metastasis or improve therapy outcomes. To do so, we need to (i) identify relevant climate factors and components, (ii) develop ‘climate biomarkers’, (iii) define ‘climate scores’, and (iv) develop strategies to prevent climate changes, stop or slow the changes, or even revert the changes.